2010
DOI: 10.3846/tede.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

New Management Systems as an Instrument of Implementation Sustainable Development Concept at Organizational Level / Naujos Valdymo Sistemos Kaip Instrumentai Įgyvendinant Darnios Plėtros Koncepciją Organizaciniu Lygmeniu

Abstract: Abstract. Diversity of contemporary management concepts, short life duration of some of them, fashion of implementing popular solutions, indiscriminate adoption of management systems in companies simultaneously with a long period of waiting for positive effects of implemented changes and decreasing involvement of employees lead to the situation in which many companies still face unresolved dilemma of choosing the right strategy of acting that ensures sustainable development of a unit. Therefore, new solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, the proposed ROI-DC method may be seen as a practical management instrument [60], facilitating economically rational decisions in the sector, thus increasing its productivity [60]. The results of the calculations indicate that BIM adoption may suffer a significant slowdown for purely economic reasons.…”
Section: Discussionmentioning
confidence: 86%
“…In conclusion, the proposed ROI-DC method may be seen as a practical management instrument [60], facilitating economically rational decisions in the sector, thus increasing its productivity [60]. The results of the calculations indicate that BIM adoption may suffer a significant slowdown for purely economic reasons.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, no work has proposed a measurement tool for the EPE management process. Ejdys and Matuszak-Flejszman [29] confirmed that one of the ways of realizing sustainable development principles at the level of an organizational unit is implementation of normalized systems elaborated by ISO. Based on the findings of Ejdys, et al [30], guidelines can be offered to both scholars and practitioners regarding the factors crucial for the improvement of the EMS.…”
Section: Introductionmentioning
confidence: 80%
“…To understand sustainable entrepreneurship, researchers must explore the pursuit of sustainable development opportunities embedded in ecosystems of entrepreneurship, its interaction with various entities, and its manifestations at the micro, macro and geographical levels [189][190][191][192][193][194][195][196]. New avenues of scientific reflection on sustainable entrepreneurship are revealed with the emergence of concepts, such as sustainable innovation [197] or responsible innovation [198].…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%